Rapid lard identification with portable electronic nose - Latief, Marsad; Khorsidtalab, Aida; Saputra, Irwan; Akmeliawati, Rini; Nordin, Anis Nurashikin; Jaswir, Irwandi; Witjaksono, Gunawan (IOP Publishing, 2017)
Human sensory systems are limited in many different regards, yet they are great sources of inspiration for development of technologies that help humans to overcome their restraints. This paper signifies the capability of our developed electronic nose in rapid lard identification. The developed device, known as E-Nose, mimics human’s olfactory system’s technique to identify a particular substance. Lard is a common pig derivative which is often used as a food additive, emulsion or shortening. It’s also commonly used as an adulterant or as an alternative for cooking oils, margarine and butter. This substance is prohibited to be consumed by Muslims and Orthodox Jews for religious reasons. A portable reliable device with an ability to identify lard rapidly can be convenient to users concerned about lard adulteration. The prototype was examined using K-Nearest Neighbors algorithm (KNN), Support Vector Machine (SVM), Bagged Trees and Simple Tree, and can identify lard with the highest accuracy of 95.6% among three types of fat (lard, chicken and beef) in liquid form over a certain range of temperature using KNN.